2021
DOI: 10.1242/dev.199551
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and staging of outer plexiform layer development in human retina and retinal organoids

Abstract: The development of the first synapse of the visual system between photoreceptors and bipolar cells in the outer plexiform layer (OPL) of the human retina is critical for visual processing but poorly understood. By studying the maturation state and spatial organization of photoreceptors, depolarizing bipolar cells, and horizontal cells in the human fetal retina, we establish a pseudo-temporal staging system for OPL development that we term OPL-Stages 0 to 4. This was validated through quantification of increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Mature RO cultures have stratified retinal layers similar to the human retina, including an outer nuclear layer (ONL) comprised solely of the nuclei of photoreceptors, an OPL comprised of synaptic junctions, and an inner nuclear layer (INL) comprised of the nuclei of second order retinal neurons and Müller glia (21) ( Fig 2b,c ). The OPL is very well conserved in the RO (22), however, the IPL and the ganglion cell layer are less well-represented in ROs because retinal ganglion cells fail to survive in great numbers to mature ages, therefore, ROs lack a pronounced layer of synaptic junctions inside of the INL (23) ( Fig 2c ). We hence refer to the layer inside of the RO INL as the lumen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature RO cultures have stratified retinal layers similar to the human retina, including an outer nuclear layer (ONL) comprised solely of the nuclei of photoreceptors, an OPL comprised of synaptic junctions, and an inner nuclear layer (INL) comprised of the nuclei of second order retinal neurons and Müller glia (21) ( Fig 2b,c ). The OPL is very well conserved in the RO (22), however, the IPL and the ganglion cell layer are less well-represented in ROs because retinal ganglion cells fail to survive in great numbers to mature ages, therefore, ROs lack a pronounced layer of synaptic junctions inside of the INL (23) ( Fig 2c ). We hence refer to the layer inside of the RO INL as the lumen.…”
Section: Resultsmentioning
confidence: 99%
“…Harvesting of MPCs was as previously described (22, 23). Supernatant from the Factory containing MPCs was passed through a cell strainer (Corning, 431750).…”
Section: Methodsmentioning
confidence: 99%
“…Cowan et al 91 compared ROs with human retina in transcriptomes, and they further characterized the functionality of ROs by measuring the light responsiveness, imaging synaptic layers, and functional synapses. Furthermore, Bharathan et al 9 applied human ROs as a model system to study the synaptogenesis in human retina, identified stages of human outer plexiform layer development, and successfully recapitulated key aspects of synaptogenesis between PRs and BCs.…”
Section: Ro Validation and Characterizationmentioning
confidence: 99%
“…Under specific culturing conditions, stem cells can be differentiated into self-assembled and layered retinal tissue spheroids that are called retinal organoids (ROs). ROs have been applied to different applications such as disease modeling,1–5 developmental biology,6–9 drug screening,10 gene therapy testing,2,11–14 and transplantation therapies 15–21. In this review, we focus on transplantation studies in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of hiPSCs, they retain the genetic background of the donor [ 363 ]. Both hiPSCs and hESCs have allowed the study of human cells which are not normally accessible to study in the human body (for example, neurons and glial cells of the human CNS) and, therefore, have boosted the possibilities in medical research employing human cell lines, permitting the study of mechanisms of human development [ 363 , 364 ]; in vitro disease modelling, including in cancer research [ 365 , 366 , 367 ]; in the development of assays and platforms for drug screening campaigns [ 355 , 368 , 369 ]; in patient stratification and in the development of cell replacement strategies [ 355 , 363 ]. The pioneer monolayer cultures gave way to organoids, spheroids, organ-on-a-chip approaches and more recently assembloids, which employ single cell types or a multitude of different cellular types [ 355 , 360 , 370 , 371 , 372 , 373 ].…”
Section: Current Challenges and Future Perspectives In Uveal Melanomamentioning
confidence: 99%